2004
DOI: 10.1038/sj.jea.7500293
|View full text |Cite
|
Sign up to set email alerts
|

Developing meaningful cohorts for human exposure models

Abstract: This paper summarizes numerous statistical analyses focused on the US Environmental Protection Agency's Consolidated Human Activity Database (CHAD), used by many exposure modelers as the basis for data on what people do and where they spend their time. In doing so, modelers tend to divide the total population being analyzed into ''cohorts'', to reduce extraneous interindividual variability by focusing on people with common characteristics. Age and gender are typically used as the primary cohort-defining attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 16 publications
(30 reference statements)
4
63
0
1
Order By: Relevance
“…Previous studies have reported age and gender as primary attributes that influence time-activity patterns in the general population. Graham and McCurdy (2004), using CHAD, identified age and gender as first-order attributes in defining statistically significant differences in time-activity patterns. These were followed by physical activity level, weather parameters, and weekend/ weekday classification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported age and gender as primary attributes that influence time-activity patterns in the general population. Graham and McCurdy (2004), using CHAD, identified age and gender as first-order attributes in defining statistically significant differences in time-activity patterns. These were followed by physical activity level, weather parameters, and weekend/ weekday classification.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the entire CHAD database provide even more support for this conclusion (Graham and McCurdy, 2003). Exposure modelers should consider these factors, particularly age, gender, season of the year, temperature, precipitation, and day-type (or at least a weekday/weekend breakdown) when choosing activity patterns for modeling purposes.…”
Section: Evaluation Of the Activity Factors Typology In The Crosssectmentioning
confidence: 99%
“…Our literature review indicates that this has never been done before. A second paper in this series (Graham and McCurdy, 2003) expands the goal of evaluating the activity typology to the entire CHAD database, covering all ages and both genders.…”
Section: External Considerationsmentioning
confidence: 99%
“…However, recording human activity patterns is an expensive and fairly intrusive process, so such data rarely exceed 10 consecutive days per individual (Graham and McCurdy, 2004). EPA's Consolidated Human Activity Database (CHAD; McCurdy et al, 2000) contains just 1 diary day from most of the individuals surveyed.…”
Section: Introductionmentioning
confidence: 99%